Haptic choice reaction time in elite judo competitors - Jakubiak, N. (University of Stirling, 2020)
Rapid reactions are an essential part of performance in most sports. In Judo the main route of information input is somatosensory, yet reaction studies have historically utilised visual or audio prompts. We have addressed the gap in knowledge pertaining to judoka`s cognitive performance on a suitable reaction test. We have designed a Judo-specific reaction device with a sensory signal that is consistent with the stream of tactile feedback in Judo. We set up a study to evaluate this novel haptic choice reaction test device and found it to be valid and reliable. We found mean reaction time to haptic signals to be shorter compared to visual ones, which is consistent with findings reported elsewhere in scientific literature. We also found evidence of judoka having achieved consistently shorter mean reaction times to haptic signals than people with experience in sports where the dominant sensory input is visual. We then used the haptic device to collect reaction time data from a cohort of elite judoka on multiple occasions. In order to sustain the judoka`s attention during the tests we introduced competition in the testing procedure. Our approach has added to the ecological validity of the method used due to the Judo-specific sensory modality of the reaction task and because the tests took place at the judoka`s training environment, during regular training sessions, and under competition pressure. We collected data under three conditions of physical intensity: Baseline (at rest), Moderate Intensity (post warm up), and Severe Intensity (post maximum effort tests). Our results show that the mean reaction time improved from Baseline by a considerable margin in a group of elite judoka at Moderate Intensity with no difference in accuracy. We found no significant difference between the mean reaction time at Baseline and Severe Intensity but there was a significant deterioration in accuracy.